(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This research emerges from the analysis of procedural alternatives granted to persons who were charged with land squatting, during the time period from january of 2015 and july of 2016. The cases of land squatting that result in conviction are identified, the study also checks if general prevention in land squatting is applied, specifically with procedural alternatives and convictions through the analysis of increase or decrease of land squatting reports. This paper also includes an assessment of more effective means to restore social order and the sensation of legal certainty. Also, it proposes alternative solutions to restore the social peace that is damaged by the commission of crimes and the restatement of the act validity. Finally, the paper exposes a contrast of the facts with the theory of general prevention.